2012
DOI: 10.1111/jdv.12007
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma epidemiology, prognosis and trends in Latvia

Abstract: There is a steady increase in melanoma incidence in Latvia with the majority of melanomas diagnosed at late stages with poor prognosis for survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
4
15
0
Order By: Relevance
“…Significant increase in melanoma incidence (from 5.1 in 1998 to 7.8 new cases per 100 000 inhabitants in 2008) was observed in Latvia and similar trend was observed in other European countries [2] where the estimated incidence of melanoma (measured per 100 000 inhabitants) varies form 19.1 in Northern Europe (NE) to 6.1 in Central and Easter Europe (CEE) with average value of 11.2 in whole Europe [3]. Melanoma mortality rates are much more similar -2.3 in CEE, 3.0 in NE and 2.3 in whole Europe.…”
Section: Introductionsupporting
confidence: 77%
“…Significant increase in melanoma incidence (from 5.1 in 1998 to 7.8 new cases per 100 000 inhabitants in 2008) was observed in Latvia and similar trend was observed in other European countries [2] where the estimated incidence of melanoma (measured per 100 000 inhabitants) varies form 19.1 in Northern Europe (NE) to 6.1 in Central and Easter Europe (CEE) with average value of 11.2 in whole Europe [3]. Melanoma mortality rates are much more similar -2.3 in CEE, 3.0 in NE and 2.3 in whole Europe.…”
Section: Introductionsupporting
confidence: 77%
“…The mean invasive MM Breslow thickness in this study was 1.29 mm (range 0.1–14.00 mm), suggesting that early detection was not compromised, despite the low NNT. The range in the literature is 0.72–6.00 . In our study, three patients had thick melanomas of 5.80, 7.40 and 14.0 mm.…”
Section: Discussionsupporting
confidence: 47%
“…The range in the literature is 0.72-6.00. 17,23 In our study, three patients had thick melanomas of 5.80, 7.40 and 14.0 mm. In each case, the patient had been referred only after multiple primary care consultations.…”
Section: Discussionmentioning
confidence: 58%
“…Stratification of 103 patients with invasive melanoma in this study by staging and Clark invasion level showed that the major part of patients were diagnosed on (Azarjana et al, 2012), 2.7 in men and 3.5 in females in Belarus, 4.4 in men and 4.6 in females in Poland (Curado et al, 2007). Being in agreement with a recent research, this observation showed melanoma incidence rates to vary considerably within European countries with the highest rates in Switzerland (19.2/100.000) (Forsea et al, 2012).…”
Section: Resultsmentioning
confidence: 99%